An Experimental Study to Replace the Thoracic Descending Aorta for Pigs with a Self-Made Sutureless Blood Vessel. (18th February 2014) - Song, Fenglin; Zhou, Wenwu; Tang, Tao; Li, Xiaobing; Wu, Xiaoming; Yang, Jinfu
Abstract : To simplify the procedure of blood vessel replacement operation and shorten the vascular anastomosis time, we developed a special artificial blood vessel which can be connected to native blood vessels without suture. The self-made sutureless blood vessel (SMSBV) was made from two titanium connectors and a Gore-Tex graft. To investigate blood compatibility and histocompatibility of the SMSBV, we carried thoracic descending aorta replacement using either SMSBV or Gore-Tex, respectively, in pigs. The aortic clamp time and the operative blood loss in the experimental group (using SMSBV) were less than those in the control group (using Gore-Tex). The whole blood hematocrit, platelet count, plasma soluble P-selectin, plasma free hemoglobin, and interleukins 2, 6 at each time point were not different significantly between the two groups. Light microscopy and transmission electron microscopy examination showed there were layers of vascular smooth muscle cells and endothelial cells adhered in the inner wall of artificial blood vessel without any signs of thrombosis. Based on the result, we have drawn the conclusion that the application of SMSBV can significantly shorten the vascular anastomosis time, reduce operative blood loss, and show good blood and tissue compatibility.